REMOTE CONTROL OF HERMETICITY MAGISTRAL GAS PIPELINES - Martyniuk, R. T. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2018)
It is known, that in the process of exploitation of main gas pipelines there are violations of impermeability, which show up as effluences of gas in surrounding, creating the threat of contamination of environment and are potentially dangerous for the origin of refusals of the system. On the surface of – rountou such effluences have the displays as temperature anomalies on a natural temperature background and anomaly of concentrations of hydrocarbons. Unlike the anomalies of other origin, in the area of effluence they practically do not rely on spatial co-ordinates and time.